Survey of knowledge, practice, and associated factors toward home management of childhood fever among parents visiting Gondar health facilities in 2022 - Assimamaw, Nega Tezera; Gonete, Almaz Tefera; Terefe, Bewuketu (Frontiers in Pediatrics, 2024)
Background: Fever is a typical symptom, usually a non-threatening sickness in children under the year of five, a devastating consequence, and a source of worry about parents. To the best of our knowledge, no research has been conducted in Ethiopia. We aimed to assess Knowledge, Practice, and associated factors towards home management of childhood fever among parents visiting Gondar Town health facilities, in 2022.Method: This multicenter institutional-based cross-sectional study was conducted in Gondar public health facilities from June 1 st -June 30 th , 2022. Participants were fathers and mothers of children aged 0-5 years. A stratified random sampling technique was used. Data were collected through face-to-face interviews using a pretested structured questionnaire.Results: Approximately, 40.2% (95% CI: 35.5%, 45.2%) of parents had good knowledge and only 12.8% (95% CI: 9.7-15.8) of parents practiced fever home management. Being married [Adjusted odds ratio [(AOR) = 2.1(1.2, 3.2)], primary and higher level of education [AOR = 2.4(1.17, 4.9)], and [AOR=2.0(1.02-4.6)], respectively, and number of children [AOR = 1.8(1.63, 2.03)] were factors associated with parental knowledge. Likewise, being married [AOR=3. 05(2.27.50-3.83)], parents who received counseling from health care providers [AOR=2.12(1.53-3.32)], and being male [AOR=2.03(1.50-3.00)] were significant predictors of practice.Inadequate level of knowledge and numerous irrational practices related to fever home management were predominant among parents, which need due emphasis. Evidence-based health education is mandatory for parents to enhance their level of knowledge and practice to effectively treat fever at home.